The role of women in peace building in Kurdish society is a field study in Sulaimani - Hussein, Asst.Prof.Dr.Shokhan Mahmoud (Sulaimani Journal for Humanities, 2026)
This research entitled (The Role of Women in Peace Building in Kurdish Society / A Field Study in Sulaimani) aims to determine the level of women's peacefulness in social and political fields, with the possibility of obstacles to their peaceful role The research community consisted of 1792 teachers of Sulaimani University. A sample of 135 people was selected through the share type. In the qualitative method, 8 women activists and defenders of women's rights in Sulaimani were selected through the ball type The most important tools used to collect data in the study are (criteria, interview forms). The research also reached some important results, including: Masculinity, Kurdish families not allowing women to participate in politics, women's abilities, characteristics and physiology) in front of women's peaceful role in Kurdish society, but there is more support for women's role in peacebuilding. Finally, in the light of the results of the study, a number of recommendations and suggestions have been made to the relevant parties and researchers.